#1**0 **

(-5)^{4} = -5 x -5 x -5 x -5 = 625

-5^{4} = -(5^{4}) = -1 x (5 x 5 x 5 x 5) = -625

geno3141 Jan 25, 2022

#2**0 **

adding onto geno, i'm going to explain the difference

negative number raised without parenthesis: you will calculate the expression WITHOUT including the negative (for example, if it was -5^4, do 5^4 first before adding the negative) and then add the negative sign to your answer. so, you would do 5*5*5*5*-1 to get -625

negative number raised with parenthesis: you will calculate the expression using -5*-5*-5*-5 to get 625.

apologize that the explanation is kind of messy. feel free to let me know if you have any other questions or concerns :]

CalTheGreat Jan 25, 2022